Presentation - González-Becerril, Juan Gabino (Papeles de Población; Vol. 22 Núm. 90 (2016), 2018)
This time the presentation is dedicated to the journal Papeles de POBLACIÓN, published by the Center of Research and Advanced Studies on the Population (CIEAP) of the Autonomous University of the State of Mexico (UAEM) which is an editorial project which has been boosted as of 1994 as a space for the dissemination, divulgation and discussion of regional, national and international demographic topics from inter- and multidisciplinary standpoints. Our journal is a quarterly publication on scientific research whose particularity and originality has served researchers with diverse backgrounds have a space for encounters and connections to think and rethink the various topics related to population. A particular characteristic of the journal is the thematic heterogeneity, the authors’ training and fields of study as well as their origin are increasingly diverse.